Remote from What? Perspectives of Distance Learning Students in Remote Rural Areas of Scotland - Macintyre, Ronald; Macdonald, Janet (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Distance learning is seen as the obvious answer for remote learners, and the use of online media is expected to overcome any access difficulties imposed by geographical distance. However, this belief may be obscuring our understanding of the role that location and individual circumstances have in shaping student experience. This paper explores the variation in experiences of remote rural students who study with the Open University (UK). The researchers found that perceptions of remoteness depended on geography, but were also relative to individual circumstances. With respect to students’ sense of connection with university staff and peers, most mentioned their contact with their personal tutor. Networks with peers were less common, a matter of concern if peer networks are integral to fostering improved retention and progression. In this particular context, distance education may be playing an important and distinctive role for remote students by providing opportunities for connections with like-minded people.